I love spelling! [ (Dorling Kindersley, 2005)
These animated adventure games feature 6 spelling games, 5,000 spelling words graded into 3 levels, and 50 spelling-pattern word groups that target problem areas. Games contain more than 100 themed word groups, test spelling, and automatically recycle misspelled words